An international survey of pain in adolescents - Swain, Michael; Henschke, Nicholas; Kamper, Steven James; Gobina, Inese; Ottová-Jordan, Veronika; Maher, Christopher Gerard (BMC public health, 2014)
A common belief is that pain is uncommon and short lived in adolescents. However, the burden of pain in adolescents is unclear because of limitations in previous research. The aim of this study is to estimate the prevalence of headache, stomach-ache and backache in adolescents and to explore the extent to which these three forms of pain coexist based upon a representative sample of adolescents from 28 countries.
Gesehen am 19.08.2020